Assessment of the state and quality of treatment in posttransplant kidney patients, by monitoring the serum redox potential - A. V. Pinchuk; I. V. Aleksandrova; M. M. Goldin; A. K. Evseyev; B. A. Sorokin (Трансплантология (Москва), 2018)
Monitoring the serum redox potential (RP) in posttransplant liver patients has previously shown that the early noninvasive diagnosis of acute graft dysfunction could be made by recording the changes in the potential measured. The changes in the steady-state potentials of a platinum electrode were studied in the treatment of patients after kidney transplantation. It has been established that the serum RP change of > 25 mW is indicative of the onset of graft dysfunction and it may be also associated with other complications or drug overdosage. An association was found between the changes in RP values and the results of treatment with plasmapheresis in the above group of patients.